Overcoming Competition From Intercropped Forages on Upland Rice With Optimized Nitrogen Input to Food Production in Tropical Region - Crusciol, Carlos A. C. [UNESP]; Portugal, José R. [UNESP]; Momesso, Letusa [UNESP]; Bossolani, Joao W. [UNESP]; Pariz, Cristiano M. [UNESP]; Castilhos, André M. [UNESP]; Costa, Nídia R. [UNESP]; Costa, Claudio H. M. [UNESP]; Costa, Ciniro [UNESP]; Franzluebbers, Alan J.; Cantarella, Heitor (Frontiers, 2020)
Intercropping forage grasses with upland rice is an alternative cropping system to improve agroecosystem diversification and could potentially enhance sustainability in tropical regions. However, nitrogen (N) immobilization and nutrient competition between rice and forage grasses could reduce rice grain yield and decrease overall productivity. Therefore, fertilizer N requirements of upland rice intercropped with forage grasses needs to be better defined. Field experiments were carried out during three growing seasons on a Typic Haplorthox soil in São Paulo state of Brazil. The experimental design was a randomized block design with a 3 × 4 factorial scheme with four replications. Treatments were cropping system [monocropped rice (Oryza sativa L.), rice intercropped with palisadegrass (Urochloa brizantha), and rice intercropped with guineagrass (Megathyrsus maximus) and sidedress N application rate (0, 40, 80, and 120 kg N ha−1). Intercropped grasses were sown between upland rice rows 30 days after rice emergence. On average, intercropping of rice with palisadegrass or guineagrass decreased rice shoot dry matter and grain yield by 11% and milled rice productivity by 10% compared with monocropped rice. Grain yield, grain protein, and milled productivity of rice increased as N application rate increased. Forage dry matter production (first and second cut) and crude protein (second cut) were greatest in the rice + palisadegrass intercropping system. Production of both forage grasses increased with up to 80 kg N ha−1 in the first cut and increased linearly with N in the second cut. Intercropping of rice with palisadegrass or guineagrass with 80 kg N ha−1 application resulted in the greatest land equivalent ratio (1.96 and 1.55, respectively). Relative N yield was greatest at 120 kg N ha−1 (220 and 173%, respectively). Although rice monocropping had greatest grain yield, intercropping systems with forage grasses were more favorable from both economic and environmental perspectives by enhancing plant diversification, nutrient cycling with forage grasses, land use production per unit area, and profitability throughout the year.
Keywords: intercropping crops; Megathyrsus maximus; Oryza sativa L; sustainable agroecosystem; Urochloa brizantha